(untitled) (Research, Society and Development, 2024)
The climacteric, the period between the reproductive and non-reproductive phases in females, is characterized by significant hormonal changes that can have a profound impact on women’s mental health, being related to depression, irritability, and anxiety. Thus, the objective of this study is to understand the state of the art of psychic changes resulting from endocrine changes related to the climacteric and their reflections on women’s quality of life. This is a systematic literature review based on the PRISMA protocol, guided by the research question: "What are the repercussions of depression in the climacteric?" conducted from June 2024 to December 2024. Twelve studies were analyzed, mostly of high quality, describing various findings related to menopausal depressive symptoms, such as age, nutritional changes, influence of hormone levels, neurotrophic factors, changes in neurotransmitter levels, and use of contraceptives. Hormonal changes in women during the climacteric lead to significant physiological changes, such as alterations in neurotrophic levels and neurotransmissions. These changes can result in psychiatric complaints, with the most reported involving mood lability and being related to hormone replacement therapy, although there is no consensus. The great variability in mood is not caused solely by the direct action of hormones but also by indirect effects such as on sleep. Detailing the pathophysiological mechanisms may enable the development of individualized therapeutic plans, resulting in more effective management for patients.